Low hepatitis C prevalence in Belgium: implications for treatment reimbursement and scale up - Amber Litzroth; Vanessa Suin; Chloé Wyndham-Thomas; Sophie Quoilin; Gaëtan Muyldermans; Thomas Vanwolleghem; Benoît Kabamba-Mukadi; Vera Verburgh; Marjorie Jacques; Steven Van Gucht; Veronik Hutse (BMC, 2019)
Abstract Background Prevalence data of chronic hepatitis C virus (HCV) infection are needed to estimate the budgetary impact of reimbursement of direct-acting antivirals (DAAs). In Belgium, the restricted reimbursement criteria are mainly guided by regional seroprevalence estimates of 0.87% from 1993 to 1994. In this first Belgian nationwide HCV prevalence study, we set out to update the seroprevalence and prevalence of chronic HCV infection estimates in the Belgian general population in order to guide decisions on DAA reimbursement. Methods Residual sera were collected through clinical laboratories. We collected data on age, sex and district. HCV antibody status was determined with ELISA and confirmed with a line-immunoassay (LIA). In specimens with undetermined or positive LIA result, HCV viral load was measured. Specimens were classified seronegative, seropositive with resolved infection, indicative of chronic infection and with undetermined HCV status according to the test outcomes. Results were standardized for age, sex and population per district, and adjusted for clustered sampling. Results In total 3209 specimens, collected by 28 laboratories, were tested. HCV seropositivity in the Belgian general population was estimated to be 0.22% (95% CI: 0.09-0.54%), and prevalence of chronic HCV infection 0.12% (95% CI: 0.03-0.41). In individuals of 20 years and older, these estimates were 0.26% (95% CI: 0.10-0.64%) and 0.13% (95% CI: 0.04-0.43), respectively. Of the total estimated number of HCV seropositive individuals in Belgium, 66% were between 50 and 69 years old. Conclusions Prevalence of HCV seropositivity and chronic infection in the Belgian general population were low and comparable to many surrounding countries. These adjusted prevalences can help estimate the cost of reimbursement of DAAs and invite Belgian policy makers to accelerate the scaling up of reimbursement, giving all chronically infected HCV patients a more timely access to treatment.